PEMBERDAYAAN PELADANG BERPINDAH: KASUS KABUPATEN KUTAI KARTANEGARA, KABUPATEN KUTAI TIMUR, DAN KABUPATEN KUTAI BARAT DI PROVINSI KALIMANTAN TIMUR - Jawatir Pardosi; Pang S. Asngari; Rudy C. Tarumingkeng; Djoko Susanto; Sumarjo . (Jurnal Penyuluhan, 2005)
Shifting cultivations (SC) who rely on their livelihood of forest resources are empowerless mainly caused by the low quality of human resources an the pressures of the forest resources utilization which covering the cultivation areas by companies. The study was aimed to formulate a model of the empowerment of SC through extension program. The respondents involved we composed of 36 extension agents and 288 shifting cultivators. Data analysis used the descriptive analysis technique such as Chi Square, Rank Spearman, and Path Analysis. The Study results showed ah: (1) factors related o empowering SC through extension that consisted of 13 variables were low; (2) applications of forestry extension in Kutai Katanegara District, East Kutai District, and West Kutai District were not able to empower the SC to realize sustainable forest; (3) the activities needed by SC are he activities, aimed to solved the SC problem, such as (a) he qualified extension about the permanent cultivation, (b) the availability of infrastructure, (c) the insurance for shifting cultivation activities, (d) the availability of specific local technology, (e) production apparatus, (f) production increase, (g) income increase, (h) market, (i) cooperation, (j) capital credit, (k) business development, (l) new business alternative; and (4) the effectively extension model hat might be able to empower the SC is the extension that became their own program and applies (a) a digging finding, and developing science and technology model, (b) interactive/convergent communication, (c) extension substances based on SC need, (d) adult learning process, and (e) community based forest management.